lexi40033
lexi40033
01-12-2017
Mathematics
contestada
How do I solve 4x-y=-9 3x-3y=0 by elimination
Respuesta :
Аноним
Аноним
01-12-2017
First multiply the first equation by -3 , you get:-
-12x + 3y = 27
now add this to second equation
3x - 3y = 0
and you eliminate y
solve for x and substitute this value of x into equation 1 to find y.
Answer Link
tynollette
tynollette
01-12-2017
4x-y=-9, so y=4x+9
replace the y in the second equation iwth 4x+9:
3x-3(4x+9)=0
3x-12x-27=0
-9x=27
x=-3
y=4x+9=4*(-3)+9=-3
Answer Link
VER TODAS LAS RESPUESTAS ( 77+ )
ACCESS MORE
Otras preguntas
The U.S. government openly stated that they would view any European interference in Latin America as
The tensions leading up to the Civil War were present at the beginning of the nineteenth century. (Points : 2) True False
What was the structure of authority within the new factories in the industrial revolution?
Which Byzantine leader restored the use of icons in 843 CE? - Theodora - Justinian - Basil - Leo III
if you change the slope in the equation y= 5x + 7 to y = 2x + 7 how will its graph change? A. It will increase at a faster rate than before B. It will increase
Two 4.0kg masses are 1.0m apart on a frictionless table. Each has 1.0μC of charge. Part A What is the magnitude of the electric force on one of the masses? What
Compare and contrast a series and parallel circuit. Give at least one way that they are alike and one way that they are different
how did geography influence the location of European colonies?
How did the issue of slavery divide the union
why is pi the best example of an exponent